Early adoption of MASB 22 (segment reporting) by Malaysian listed companies - Wan Hussin, Wan Nordin; Che Adam, Noriah; Lode, Nor Asma; Kamardin, Hasnah (Malaysian Accountancy Research and Education Foundation, 2003)
Listed companies in Malaysia have to adhere to a new standard of segment reporting (MASB 22) for their financial statements beginning on or after 1 January 2002. The reporting and disclosure requirements under MASB 22 are similar, in all materials aspects, to the requirements under the revised International Accounting Standard (IAS) 14. Anticipating that some Malaysian companies might adopt MASB 22 earlier, this study seeks to find out how pervasive is early adoption in Malaysia and the disclosure practices among the early adopters. Based on a sample of 32 early adopters, the findings show that less than half of the companies comply fully with the MASB 22 requirements. The most glaring disclosure deficiency is the failure to disaggregate non-cash expenses other than depreciation and amortization by reportable segments. Other deficiencies include non-disclosure of capital expenditure and investment in equity method associates by reportable segments, and basis for inter-segment pricing.